A Social Cognitive Theory of sustainability empathy. (May 2016) - Font, Xavier; Garay, Lluis; Jones, Steve
Graphical abstract: Highlights: Sustainability empathy depends on the attachment placed to valued objects. Foci are beneficiary groups (self, others, biosphere) and lifestyle principlism. Individualism leads to self-enhancement and out-group self-transcendence. Collectivists are communal with their self-defined in-group. Perceived efficacy on personal, proxy and collective agency explain foci. Abstract: Social-Cognitive Theory is used to test the argument that the motivations behind sustainable tourism, and the types of sustainable actions undertaken, depend on one's empathy towards sustainability. Latin American businesses were surveyed about their motivations for acting sustainably and any sustainability actions undertaken. Based on their responses, TwoStep cluster analysis found four clusters (cost, legitimisation, biospheric, and lifestyle). Acceptance of responsibility to be more sustainable depends on one's level of empathy with, and attachment to, sustainability, explained by a beneficiary focus (personal norms that drive one to act to help oneself or others) and a cultural focus (acting in response to individualistic or collectivistic social norms). Lifestyle businesses are argued to be culturally individualistic but self-transcendent in benefit focus.